Brazil and World Bank in face of the environmental question - Vilarinho, Carlyle R. O. (Universidade Estadual Paulista / UNESP, 2009)
The environmental question emerged, in the 70's, as an important variable in the appreciation of development projects on the part of Development Multilateral Banks. Beiry criticized by the international community, Brazil faces preocupations and demands from the World Bank.